Gear Skiving and Tool Design Method for Manufacturing Tangent Quadruple Circular-arc Harmonic Flexsplines - Guo Erkuo; Xu Jia; Hong Yang; Liu Chang; Hu Lele (Jixie chuandong)
The tangent quadruple circular-arc harmonic gear has the advantages of strong load capacity and transmission stability. In order to meet requirements of high efficiency and precision machining of tangent quadruple circular-arc harmonic gears, a method of gear skiving and manufacture of the tangent quadruple circular-arc harmonic flexspline was presented based on establishing the two-parameters conjugated tooth surface of the gear tooth. The kinematic model of skiving and the mathematical model of the tangent quadruple circular-arc harmonic flexspline were established. Then the meshing equation of the two-parameters conjugated tooth surface between the generative cutter and the gear tooth surface was derived. The accurate cutting edges on the normal surface of the skiving tool were obtained by solving conjugated tooth surface and constructing normal equation of the tool. The skiving tool was designed and manufactured by using the cutting edges on the end surface. The simulation and cutting experiment have been carried out to verify the effectiveness of the proposed tool design method, which has a higher accuracy for machining the tangent quadruple circular-arc harmonic flexspline. The results could provide guidance for the high efficiency and high precision manufacturing of tangent quadruple circular-arc harmonic flexsplines.